2015
DOI: 10.1111/apa.13018
|View full text |Cite
|
Sign up to set email alerts
|

From emergent literacy to reading: how learning to read changes a child's brain

Abstract: Behavioural and neuroimaging correlates for linguistic ability and literacy exposure support the engagement of neural circuits related to reading acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 66 publications
1
58
0
Order By: Relevance
“…The risk of developing learning difficulties in childhood has also been shown to be three times higher in children who were born preterm . This finding supports longitudinal neuroimaging studies that suggest that preterm birth features late maturation of the brain regions related to the frontal lobe and delays in connecting these frontal cortices to the parietal and occipital lobes , which play a critical role in both language and reading acquisition . This topic is extremely timely, as in vitro fertilisation techniques are increasingly being used.…”
supporting
confidence: 62%
“…The risk of developing learning difficulties in childhood has also been shown to be three times higher in children who were born preterm . This finding supports longitudinal neuroimaging studies that suggest that preterm birth features late maturation of the brain regions related to the frontal lobe and delays in connecting these frontal cortices to the parietal and occipital lobes , which play a critical role in both language and reading acquisition . This topic is extremely timely, as in vitro fertilisation techniques are increasingly being used.…”
supporting
confidence: 62%
“…This has been confirmed by studies on illiterate people, in whom less cerebral lateralization of language functions is observed, and in whom a similar phenomenon is suspected to exist within the scope of visual-spatial functions in comparison to literate people (Ardila et al, 2010). Researchers also claim that with the use of adequate exercises it is possible to change the cerebral organization of reading (Shaywitz, & Shaywitz, 2004;Horowitz-Kraus, & Hutton, 2015) and that the sole process of learning how to use script changes the cerebral organization of other functions, e.g., visual perception (James, Jao, & Berninger, 2016).…”
Section: Effects Of Learning To Read and Writementioning
confidence: 84%
“…The participant in this study also demonstrated a similar pattern, with large clusters and intense activity in the frontal and parietal regions, as seen in the acquisition of a second language in adulthood. These activations in the frontal areas may be associated with a support system for learning, with the greater use of executive functions of self‐monitoring and executive attention (Horowitz‐Kraus & Hutton, ). Indeed, the participant showed intense bilateral activation in three areas related to effortful attention and learning: the superior parietal lobule, the posterior‐medial frontal, and the superior frontal gyri.…”
Section: Discussionmentioning
confidence: 99%